Perforaciones intestinales (1962)
348 cases are studied of perforated abdominal injuries treated at the Hospital San Juan de Dios of Bogotá during the years 1953-1960. There has been a decrease of 8.6 per cent mortality compared with statistics compiled in 1940. A comparison is made with similar studies published in the United States. The management of these cases is described.